Age effects in the Okun's law within the Eurozone - Oliver Hutengs; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
We estimate Okun coefficients for five different age cohorts for several Eurozone countries. We find a stable pattern for all countries: The relationship between business-cycle fluctuations and the unemployment rate is the strongest for the youngest cohort and gets smaller for the elderly cohorts.
Keywords: E24; F50; C23; 330; Okun's law; labor market; youth unemployment